2020
DOI: 10.1111/cas.14609
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics for severe adverse drug reactions induced by molecular‐targeted therapy

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Molecular-targeted drugs may interfere with molecules that are overexpressed in target cancer cells. These drugs may cause life-threatening ADRs which deserve particular PGx attention [11,124].…”
Section: Cancermentioning
confidence: 99%
“…Molecular-targeted drugs may interfere with molecules that are overexpressed in target cancer cells. These drugs may cause life-threatening ADRs which deserve particular PGx attention [11,124].…”
Section: Cancermentioning
confidence: 99%
“…However, despite these findings, the pathogenic role of the IL-17 pathway in primary and ICI-induced pituitary (and hypothalamic) dysfunction needs to be better clarified. Finally, a potential role of some gene polymorphisms in prompting ICI-related toxicity has been suggested [ 6 , 65 ]. Some CTLA-4 polymorphisms are commonly associated with autoimmune disorders, including endocrinopathies (i.e., T1DM, Graves’ disease, autoimmune hypothyroidism, and Addison’s disease) [ 6 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only in a few studies has a linkage between PD-1 polymorphisms and T1DM has been suggested, while PD-L1 polymorphisms were found to be linked to T1DM, Graves’ disease, and Addison’s disease [ 6 , 66 ]. Based on these data and the well-documented association between some germline genetic variants and adverse events induced by anticancer agents [ 67 ], an association between specific gene polymorphisms of immune checkpoints and the development of ICI-induced toxicities has been postulated [ 6 , 65 ]. However, studies on the role of gene polymorphism in ICI-induced hypothalamic–pituitary dysfunction are needed.…”
Section: Discussionmentioning
confidence: 99%
“…This may be done with the use of small molecules, monoclonal antibodies, therapeutic cancer vaccines, or gene therapy which function to ultimately promote cell death (16). Molecular targeted therapy rarely produces adverse side effects due to its personalization towards the patients' genetic profile (17). Patients may benefit from a combination of chemotherapy and molecular targeted therapy and increase the effectiveness of treatment.…”
Section: Molecular Targeted Therapymentioning
confidence: 99%